2017
DOI: 10.3389/fpsyg.2017.01496
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Sinus Arrhythmia Activity Predicts Internalizing and Externalizing Behaviors in Non-referred Boys

Abstract: Atypical respiratory sinus arrhythmia (RSA), a biomarker of emotion dysregulation, is associated with both externalizing and internalizing behaviors. In addition, social adversity and gender may moderate this association. In this study, we investigated if RSA (both resting RSA and RSA reactivity in an emotion regulation task) predicts externalizing and/or internalizing behaviors and the extent to which social adversity moderates this relationship. Two hundred and fifty-three children (at Time 1, mean age = 9.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…The null results for PNS reactivity regarding family environmental factors may be usefully considered in light of controversies regarding measurement of PNS reactivity. Some laboratories have operationalized PNS reactivity in terms of vagal withdrawal (e.g., Bush, Alkon, et al, 2011; Fox, Hammond, & Mezulis, 2018; Obradović et al, 2010), while other laboratories have operationalized PNS reactivity in terms of any change from baseline (withdrawal or augmentation; Beauchaine, Gatz-Kopp, & Mead, 2007; El-Sheikh et al, 2009; Kuhn, Ahles, Aldrich, Wielgus, & Mezulis, 2018; Zhang, Fagan, & Gao, 2017). The current signal detection analyses employed both vagal withdrawal (conceptualized here as high PNS reactivity) and vagal augmentation (conceptualized here as low PNS reactivity) as dependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…The null results for PNS reactivity regarding family environmental factors may be usefully considered in light of controversies regarding measurement of PNS reactivity. Some laboratories have operationalized PNS reactivity in terms of vagal withdrawal (e.g., Bush, Alkon, et al, 2011; Fox, Hammond, & Mezulis, 2018; Obradović et al, 2010), while other laboratories have operationalized PNS reactivity in terms of any change from baseline (withdrawal or augmentation; Beauchaine, Gatz-Kopp, & Mead, 2007; El-Sheikh et al, 2009; Kuhn, Ahles, Aldrich, Wielgus, & Mezulis, 2018; Zhang, Fagan, & Gao, 2017). The current signal detection analyses employed both vagal withdrawal (conceptualized here as high PNS reactivity) and vagal augmentation (conceptualized here as low PNS reactivity) as dependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, girls high on SNS reactivity were more likely to develop ASB in the context of marital conflict (El-Sheikh, 2005a;. Inconsistencies among girls were evident across low-and high-risk samples, cross-sectional and longitudinal studies, among children and adolescents, and across several measures of SNS reactivity (see El-Sheikh, 2005a;Sijtsema et al, 2015;Wagner & Abaied, 2015, 2016 Most studies (n = 12 out of 17) on interactions between baseline PNS and social risk showed that lower (El-Sheikh, Hinnant, Erath, & El-Sheikh, 2015;Zhang, Fagan, & Gao, 2017) as well as higher (Dierckx et al, 2011;Scarpa et al, 2008;Shannon et al, 2007) PNS activity exacerbated the positive relation between social risk and ASB. Children with lower baseline PNS functioning were more likely to show ASB in the context of parental problem drinking (El-Sheikh, 2005b), material conflict , and harsh parenting (Hinnant et al, 2015).…”
Section: Sns Functioningmentioning
confidence: 99%
“…While studies among boys consistently found interactions between PNS baseline activity and social risk (Dyer, Blocker, Day, & Bean, 2016;Gordis et al, 2010;Hinnant et al, 2015;Zhang et al, 2017), most studies did not find significant interaction effects among girls (Dyer et al, 2016;Gordis et al, 2010;Zhang et al, 2017). The two studies that did report significant biosocial interactions among girls, found either a negative relationship between social risk and ASB among girls with lower levels of PNS activity (Hinnant et al, 2015), or a stronger relation between familial risk and ASB for girls with higher PNS activity (Eisenberg et al, 2012).…”
Section: Sns Functioningmentioning
confidence: 99%
“…Many studies have found that lower baseline RSA is linked to internalizing problems (Forbes et al, 2006; Dietrich et al, 2007; Wei et al, 2017), while in contrast, other studies have found that lower baseline RSA is not linked to internalizing problems in children and adolescents (El-Sheikh et al, 2011; Hinnant and El-Sheikh, 2013). One possible explanation for these conflicting findings is that the association between baseline RSA and internalizing problems might partly be affected by environmental variables.…”
Section: Introductionmentioning
confidence: 97%